The Black Sea in the light of new archaeological data and theoretical approaches : proceedings of the 2nd International Workshop on the Black Sea in antiquity held in Thessaloniki, 18-20 September 2015 - Manōledakēs, Manolēs, (Archaeopress archaeology., 2016)
'The Black Sea in the Light of New Archaeological Data and Theoretical Approaches' contains 19 papers on the archaeology and ancient history of the Black Sea region, covering a vast period of time, from the Early Iron Age until the Late Roman - Early Byzantine Periods. The majority of papers present archaeological material that has come to light during the last few years, in excavations that have been taking place in several parts of Pontus. Additionally, there are papers that present theoretical approaches to historical issues concerning the Black Sea, its local peoples, cultural aspects or specific sites, while at the end there is as well as a section on the connections between the Black Sea and northern Greece.